Disseminated Histoplasmosis-Associated Cardiac Tamponade in a Patient With Acquired Immunodeficiency Syndrome - Priya Ramcharan MBBS; Arun Katwaroo MBBS; Matthew Maharaj MBBS; Valmiki Seecheran MBBS, MSc; Rajeev Seecheran MBBS, MHA; Lakshmipathi Peram MBBS; Stanley Giddings MBBS; Naveen Seecheran MBBS (MD), MSc, FACP, FRCP(E), FACC, FAHA, FESC, FSCAI (Journal of Investigative Medicine High Impact Case Reports)
We describe a case of a 57-year-old Caribbean-Black male with a medical history of concealed human immunodeficiency virus/acquired immunodeficiency syndrome who presented with cardiac tamponade (CT) secondary to disseminated histoplasmosis. The patient underwent emergent pericardiocentesis with immediate normalization of his hemodynamic status and resolution of obstructive shock. The clinician should consider atypical etiologies of CT, such as opportunistic infections in patients with HIV/AIDS.